Contributing factors: implementation of poor population data collection - Arifah, Umi; Suwitri, Sri; Larasati, Endang; Yuwanto, Yuwanto (Management and Entrepreneurship: Trends of Development, 2020)
The purpose of this study was to examine the implementation of data collection on the poor carried out by TKP2KDes (Village Poverty Reduction Coordination Team) and to identify the factors that contributed to the collection of TKP2KDes poor population in Kebumen District. Identification related to factors that contribute to the research of poor population data collection is based on the framework of public administration. Methodology: descriptive qualitative method is used in analyzing research phenomena. Kebumen District Regulation No. 31 of 2014 concerning Criteria and Procedures for Data collection on the Poor is used as a reference in examining the stages of the implementation of data collection on the TKP2KDes poor population in Kebumen District. The TKP2KDes poverty data in this study contributed to providing a picture of poverty conditions in Kebumen District. The Miles, Huberman, and Saldana models used in data analysis are performed by condensing data, presenting data, and drawing conclusions. The research findings show that the contributing factors related to leadership, budget, program implementation, commitment, and human resources have not been running optimally. TKP2KDes poverty data has not been used as poverty data in developing poverty alleviation programs in the regions and monitoring and evaluation have not been carried out continuously in Kebumen District.JEL Classification: D73, I28.